Uma reflexão sobre a formação da identidade feminina em mulheres vítimas de violência doméstica - Lima, Ana Paula Mallet [UNIFESP] (2010)
Domestic violence against women in Brazil and the world is a matter of concern at the present time. This is a surprisingly contemporary phenomenon, although it has occurred throughout the history of mankind. Violence in relations between the two shows a dynamic of power and a kind of effect which are present in domination and submission characterized by the gender differences that can be seen to the extent that the internal division of roles is configured in rights and duties with privileges to one of the parties within the family environment. Work in human sciences has given us an understanding of the context of psychological damage involving women in situations of domestic violence, as well as the historical and social context that seem to point to a woman in need of mentors for those who have a condition of dependence and co – dependency. This dissertation, which is based on psychology combined with psychiatry, aims to investigate whether battered women had mothers mothers that were abused. We have investigated some aspects of female identity and motherhood that are related to the growth and training of women in situations of family violence, as well as posttraumatic stress disorder (PTSD) as it occurs in these cases. The methodology is the qualitative technique of a semi-structured script of questions that guide the research subjects. These were used as tools to diagnose whether or not there is PTSD and also its severity, and used for the presence of a history of abuse and trauma during childhood and adolescence of these women. The participants were patients in the outpatient clinic a facility for the treatment of violence. Also patients were referred from the Womens Police Unit, from a collection of survey data and from other author. Data analysis was based on the theoretical resources-historical and anthropological, as well as fundamentals of analytical psychology. The results showed that participants had a family structure based on episodes or in the context of violence, where the mother-daughter relationship is important in the transmission of gender inequality, and is considerably preconditioned with PTSD due to emotional problems from this violent environment in childhood. At the conclusion of this study, we arrived at the idea of this paper on the importance of the maternal role in the formation of female identity, since the mother carries the standard historical-social and cultural status of women and also a marked psychological the context of violence, sharing with her daughter, acting or receiving violence, directly or indirectly through the psychological, which is home to other forms of domestic violence. Through this framework, there is a structure prone to psycho trigger PTSD in adulthood their daughters, victims of domestic violence.